Mengyun Wang - Modeling Water Quality in Dynamic River Systems: Simulating Nutrients and Emerging Contaminants Under Variable Flow Conditions. (Jornada de Jóvenes Investigadores del I3A, 2025)
Modeling Water Quality in Dynamic River Systems: Simulating Nutrients and Emerging Contaminants Under Variable Flow Conditions.